Integrating electrochemical and bioelectrochemical systems for energetically sustainable treatment of produced water - Gunda Mohanakrishna (17115679) (2021)
Pollutants present in produced water (PW) are recalcitrant in nature and difficult to treat with simple processes. Energetically sustainable and novel approach was developed by integrating electrochemical cell (EC, Primary process) and microbial fuel cell (MFC, secondary process) to treat PW. Five different current densities (26, 36, 48, 59 and 71 mA/cm2) were applied in independent EC experiments (4 h). The effluents from each EC operation was further treated by MFC (10 h), to harness bioelectricity. Operational variations were maintained only in EC phase and kept MFC phase similar. This integration revealed that the extent of bioelectricity generation depends on the electrochemical oxidation of EC process. Overall, maximum power generation of 2.74 mW was registered with EC-effluent from 48 mA/cm2. The integration also showed highest TPH removal efficiency of 89% (EC, 305 mg/L; MFC, 317 mg/L) and COD removal efficiency of 89.6% (EC, 2160 mg/L; MFC, 1960 mg/L) at 71 mA/cm2. Other pollutants of PW, such as sulfates and TDS also removed efficiently (sulfates, 42.6%; TDS, 34.3%). Cyclic voltammetric (CV) and derivative analysis of the anodic biofilm were correlated well with MFC performance during different EC-effluents as substrate, indicating NADH involvement in bioanodic electron transfer. The balance between energy utilization in EC and bioelectricity generation by MFC was depicted that the integration of EC and MFC results in net positive energy. Maximum net power generation of 565 mWh (350 mL of anode volume) was resulted by integration. This integration depicts its potential to generate 1615 Whm−3 from the treatment of 1KL PW. Other Information Published in: Fuel License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.fuel.2020.119104